Kelimpahan Thrips parvispinus Karny dan Musuh Alaminya pada Tanaman Cabai Besar (Capsicum annuum L.) - I NYOMAN WIJAYA; I GEDE PUTU WIRAWAN (Agrotrop : Journal on Agriculture Science, 2022)
The Abundance of Thrips parvispinus Karny and Its Natural Enemies in Chili Crops (Capsicum annuum L.). This aims of the research is to search the abundance of T. parvispinus Karny and its natural enemies on chili crops (Capsicum annuum.L). The research started from May 2021 to August 2021, located in Selat Village, Banjarangkan District, Klungkung Regency, and at the Plant Pest Laboratory, Faculty of Agriculture, Udayana University. The study was conducted using a descriptive method by conducting a diagonal survey of 20 samples of chili plants that were attacked by T. parvispinus. Observations were made by observing 10 leaves and 10 flowers of chili plants. The results showed that the abundance of T. parvispinus in the vegetative and generative phases fluctuated where the highest population of T. parvispinus occurred in plants aged 10 WAT with an average population of 17,57 individuals per plant then decreased in plants aged 11 WAT with an average population 11,12 individuals. There were two species of predators that preyed on T. parvisvinus, namely Coccinela transversalis with an average population of 23.3 and Chrysoperla carnea with an average of 18,2 individuals. There was one of nymph parasitoid to suppress the development of T. parvispinus namely Ceranisus spp with an average parasitization level 9,8 %.